Athenion of Athens Revisited - Antela Bernárdez, Borja, 1977- (2015)
The usual view historiography has taken into account about the controversial data concerning the politician Athenion of Athens, mainly based in the perspective of one of Posidonius' extant fragments, has portrayed Athenion as a tyrant. A close look at the information we have about him and his policies allows to ask new questions and to get a deeper perspective about the complex age of Athenian history that led the city to take part in the Ist Mithridatic War on the Pontic side, against Rome.
Keywords: Dictadores; Atenas (Grecia) -- Historia